2020
DOI: 10.22159/ijcpr.2020v12i5.39771
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis, Antioxidant, Anti-Inflammatory and Antinociceptive Effects of Acetone Extract of Algerian Solenostemma Argel (Delile) Hayne Leaves

Abstract: Objective: To investigate the qualitative composition of the acetonic extract from leaves of S. argel (AESA) and their anti-inflammatory and analgesic properties in vivo. Methods: AESA profile was established by UHPLC/DAD/ESI-MS2. AESA was subjected to the acute oral toxicity study according to the OECD-420 method. Antioxydant activity of AESA was performed by DPPH radical scavenging assay. Anti-inflammatory effects of AESA were determined in two animal models: carrageenan-induced paw edema in rats and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Al-Juhaimi et al [ 32 ] stated that the antioxidant activity of argel extract was due to the presence of phenolic acids, flavones, glycosylated flavonoids, polyphenols, b-carotene, b-sitosterol, monoterpenes, pregnenes, and pregnan. Benmaarouf et al [ 21 ] stated that the high content of flavonoids such as rutin, kaempferol-3-o-rutinoside, kaempferol-3-o-diglucoside-7-o-glucoside, astragalin, and kaempfero in Solenostemma argel imparted its antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Al-Juhaimi et al [ 32 ] stated that the antioxidant activity of argel extract was due to the presence of phenolic acids, flavones, glycosylated flavonoids, polyphenols, b-carotene, b-sitosterol, monoterpenes, pregnenes, and pregnan. Benmaarouf et al [ 21 ] stated that the high content of flavonoids such as rutin, kaempferol-3-o-rutinoside, kaempferol-3-o-diglucoside-7-o-glucoside, astragalin, and kaempfero in Solenostemma argel imparted its antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of flavonoids and related polyphenols in Solenostemma argel extract may be responsible for its anti-inflammatory activity [ 39 ]. Benmaarouf et al [ 21 ] stated that the anti-inflammatory activity of Solenostemma argel may be due to the inhibition of the release of anti-inflammatory mediators occurring during the intermediate and second phases of edema formation, such as bradykinin and prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are similar to those of Rawat et al who disclosed that the methanolic extract of Kigelia pinnata leaves at 400 mg/kg bw inhibited the average weight of wet cotton pellets by 45.15% and that of dry cotton pellets by 53.6% [25]. In addition, other authors showed that at 400 mg/kg bw, the acetone extract of Solenostemma argel leaves significantly (p<0.05) reduced wet cotton peletts by 67.74% and that of dry cotton pellet by 70.58% [26]. The assessment of rats body weight during granuloma formation induced by the cotton pellets indicated a decrease in rats body weight in the normal saline group.…”
Section: Discussionmentioning
confidence: 99%